2011
DOI: 10.1111/j.1469-8749.2011.04165.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral alterations in somatosensory cortical processing in hemiplegic cerebral palsy

Abstract: MACS Manual Ability ClassificationMETHOD We recorded somatosensory evoked magnetic fields in response to hand area stimulation from eight adolescents with hemiplegic CP (five females and three males; mean age 14y 6mo, SD 2y 3mo) and eight age-and sex-matched healthy comparison adolescents (mean age 15y 4mo, SD 2y 4mo). All participants in the CP group had purely subcortical brain lesions in magnetic resonance images. RESULTSThe somatosensory representation of the affected limb was contralateral (i.e. ipsilesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 26 publications
6
43
2
Order By: Relevance
“…Functional alterations in the magnetic evoked responses observed here have also been previously reported after the tactile stimulation of fingers and after the electrical stimulation of the median nerve in HCP children with subcortical lesions (Nevalainen et al, 2012). These alterations include missing deflections, aberrant morphology, and different distances in the localized SEFs components between CP and TD patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Functional alterations in the magnetic evoked responses observed here have also been previously reported after the tactile stimulation of fingers and after the electrical stimulation of the median nerve in HCP children with subcortical lesions (Nevalainen et al, 2012). These alterations include missing deflections, aberrant morphology, and different distances in the localized SEFs components between CP and TD patients.…”
Section: Discussionsupporting
confidence: 85%
“…Aside from motor and postural impairments, children with SCP frequently experience sensory deficits such as altered tactile, proprioceptive, kinesthetic, and pain awareness (Van Heest et al, 1993; Cooper et al, 1995; Krumlinde-Sundholm and Eliasson, 2002; Sanger and Kukke, 2007; Wingert et al, 2009; Riquelme et al, 2011). Recent functional neuroimaging studies have reported altered SS processing in SCP individuals as measured by SS-evoked potentials or fields in terms of amplitude, morphology, frequency power, or somatotopy (Riquelme and Montoya, 2010; Kurz and Wilson, 2011; Teflioudi et al, 2011; Guo et al, 2012; Nevalainen et al, 2012; Pihko et al, 2014; Riquelme et al, 2014). In a recent magnetoencephalography (MEG) study, Pihko et al (2014) found that suppression and rebound of alpha and beta cortical activity to contralateral stimulation were smaller in the lesioned compared to the intact hemisphere in hemiplegic CP (HCP) children, while they did not find any difference between the hemispheres of typically developing (TD) children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Aside from atypical hemispheric dominance of motor control, other evidence demonstrates atypical interactions between hemispheres through transcallosal fibers. 2 Additional studies, such as the Nevalainen et al MEG study, 5 have examined cortical somatosensory reorganization in children with cerebral palsy. Such studies suggest that somatosensory representation of the affected limb can be represented bilaterally, by both the affected and unaffected hemispheres, 5 although other patterns of somatosensory reorganization have been reported.…”
mentioning
confidence: 99%
“…The latest PNME is perhaps the shaking body attack 5 and doubtless more will be described and reduce the number of unclassified PNMEs, and so satisfy the 'splitters'. By contrast, 'lumpers' might wish to add in infantile masturbation to create an all-encompassing benign non-epileptic episodic contractions in infancy (Nechay A, King MD, Stephenson JBP, personal communication 2009).…”
mentioning
confidence: 99%